(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This systematic review synthesises findings from 48 peer-reviewed studies published between 2015 and 2026 on the wellbeing, occupational stress, and workplace experiences of working women. Drawing on a Scopus-indexed corpus, the review identifies seven key thematic areas: psychological wellbeing and mental health, workplace harassment and bullying, work-life balance and family conflict, gender inequality, industry-specific occupational stress, physical health and body image, and relationships and domestic life. Findings consistently highlight that working women face compounding stressors arising from dual role demands, hostile work environments, gender-based inequalities, and inadequate organisational support. Evidence-based interventions such as mindfulness, internet-based therapies, flexible work policies, and physical activity programmes are identified as promising strategies to improve wellbeing outcomes. The review calls for targeted organisational policies and broader structural reforms to promote equitable, healthy workplaces for women across sectors and geographies.